(untitled) (Ustozlar uchun, 2025)
The liver is one of the most metabolically active and functionally diverse organs in the human body. It performs crucial roles in metabolism, detoxification, synthesis of plasma proteins, and regulation of biochemical pathways necessary for homeostasis. This paper provides a comprehensive overview of the physiological processes of the liver, focusing on its metabolic, synthetic, excretory, and immunological functions. Furthermore, the study discusses the regulatory mechanisms that maintain hepatic function, highlighting the significance of hepatocytes, enzymatic systems, and hormonal control. Understanding the physiology of the liver is fundamental for diagnosing and managing hepatic disorders and for advancing therapeutic strategies in hepatology.